Organic or organised: an interaction analysis to identify how interactional practices influence participation in group decision meetings for residency selection - Matthijs de Hoog; Lokke Gennissen; Anne de la Croix; Karen Stegers-Jager; Jacqueline de Graaf; Cornelia R M G Fluit (BMJ Open, 2019)
Objectives This study aims to shed light on interactional practices in real-life selection decision-making meetings. Adequate residency selection is crucial, yet currently, we have little understanding of how the decision-making process takes place in practice. Since having a wide range of perspectives on candidates is assumed to enhance decision-making, our analytical focus will lie on the possibilities for committee members to participate by contributing their perspective.Design We analysed interaction in seven recorded real-life selection group decision meetings, with explicit attention to participation.Setting Selection meetings of four different highly competitive specialties in two Dutch regions.Participants 54 participants discussed 68 candidates.Methods To unravel interactional practices, group discussions were analysed using a hybrid data-driven, iterative analytical approach. We paid explicit attention to phenomena which have effects on participation. Word counts and an inductive qualitative analysis were used to identify existing variations in the current practices.Results We found a wide variety of practices. We highlight two distinct interactional patterns, which are illustrative of a spectrum of turn-taking practices, interactional norms and conventions in the meetings. Typical for the first pattern—‘organised’—is a chairperson who is in control of the topic and turn-taking process, silences between turns and a slow topic development. The second pattern—‘organic’—can be recognised by overlapping speech, clearly voiced disagreements and negotiation about the organisation of the discussion. Both interactional patterns influence the availability of information, as they create different types of thresholds for participation.Conclusions By deconstructing group decision-making meetings concerning resident selection, we show how structure, interactional norms and conventions affect participation. We identified a spectrum ranging from organic to organised. Both ends have different effects on possibilities for committee members to participate. Awareness of this spectrum might help groups to optimise decision processes by enriching the range of perspectives shared.